This could hurt [compact disc, unabridged] : a novel - Medoff, Jillian (Harper Audio, 2018)
Rosa Guerrero beat the odds as she rose to the top of the corporate world. An attractive woman of a certain age, the longtime chief of human resources at Ellery Consumer Research is still a formidable presence, even if her most vital days are behind her. A leader who wields power with grace and discretion, she has earned the devotion and loyalty of her staff. No one admires Rosa more than her doting lieutenant Leo Smalls, a benefits vice president whose whole world is Ellery. While Rosa is consumed with trying to address the needs of her staff within the ever-constricting limits of the company's bottom line, her associate director, Rob Hirsch, a middle-aged, happily married father of two, finds himself drawing closer to his 'work wife', Lucy Bender, an enterprising single woman searching for something - a romance, a promotion - to fill the vacuum in her personal life. For Kenny Verville, a senior manager with an MBA, Ellery is a temporary stepping-stone to bigger and better places.